Oxidation of Phenolic Wastewater by Fenton’s Reagent - Faisal, Ibtihage (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Phenol oxidation by Fenton’s reagent (H2O2 + Fe+2) in aqueous solution has been studied for the purpose of learning more about the reactions involved and the extent of the oxidation process, under various operating conditions. An initial phenol concentration of 100 mg/L was used as representative of a phenolic industrial wastewater. Working temperature of 25C was tested, and initial pH was set at 5.6 . The H2O2 and the Fe+2 doses were varied in the range of (H2O2/Fe+2/phenol = 3/0.25/1 to 5/0.5/1). Keeping the stirring speed of 200 rpm. The results exhibit that the highest phenol conversion (100%) was obtained under (H2O/Fe+2/phenol ratio of 5/0.5/1) at about 180 min. The study has indicated that Fenton’s oxidation is first order with respect to the phenol concentration and the rate constant K, was found to be 0.0325s-1 .